Predictors influencing neurodevelopment during the infancy of term infants - Zhang, Yixia; Hu, Bo; Jin, Zhipeng; Wang, Shaowen; Wang, Qingqing; Nie, Jiyu (Frontiers in Pediatrics, 2025)
ObjectivesThis study aimed to determine the influencing factors of neurodevelopment of term infants (37–41 6/7 weeks) aged <1 year to provide a basis for neurodevelopment monitoring and management of term infants.Study designA total of 327 term infants aged 4–12 months who visited the outpatient department of Child Health Care at the Children’s Hospital Affiliated to Zhengzhou University from December 2023 to June 2024 were included. The Developmental Behavior Assessment Scale for Children aged 0–6 years was used to assess the neurodevelopment of infants who underwent routine physical examination. Univariate and multiple linear regression analyses of the influencing factors on neurodevelopment were conducted.ResultsGreater gestational age (GA) and birth weight (BW) were independent predictors of a higher total development quotient (TDQ) score (t = 2.191 and 2.462, respectively; both p < 0.05). Overweight and a trend toward overweight in infants were predictors of a low TDQ score (t = −2.663, p = 0.008). The R2 value was 0.135 (adjusted R2 = 0.116) with a root mean square error (RMSE) of 7.138, showing that 13.5% of the TDQ score is explained by differences in GA, BW, and body mass index (BMI). Increased GA and maternal folic acid supplementation prior to pregnancy were independently associated with a higher gross motor score (t = 2.377 and −2.128, respectively; both p < 0.05). Conversely, infant overweight status or a trend toward overweight was associated with a lower gross motor score (t = −2.466, p = 0.014). Greater GA and older age were independent predictors of a higher fine motor score (t = 2.155 and 4.502, respectively; both p < 0.05). Longer days of neonatal intensive care unit (NICU) admission during the neonatal period were a predictor of a lower fine motor score (t = −3.528, p < 0.001). Greater GA was an independent predictor of a higher adaptability score (t = 3.245, p < 0.001). Older age was a predictor of a lower adaptability score (t = −4.113, p < 0.001). Maternal junior college or above was an independent predictor of a higher language score (t = 2.350, p = 0.019). Older age and gestational hypertension were predictors of a lower language score (t = −5.553 and −2.604, respectively; both p < 0.05). No factor was found to be an independent predictor of the social behavior score.ConclusionGA, BW, BMI, days of NICU admission, prenatal folic acid supplementation of mothers, gestational hypertension, and maternal educational level were influencing factors in the neurodevelopment of infants aged 4–12 months.